In vitro studies on flubromazolam metabolism and detection of its metabolites in authentic forensic samples. Issue 8 (10th February 2017) - Noble, Carolina; Mardal, Marie; Bjerre Holm, Niels; Stybe Johansen, Sys; Linnet, Kristian
Abstract : Flubromazolam is a triazole benzodiazepine with high potency and long‐lasting central nervous system depressant effects; however, limited data about its pharmacokinetics are available. Here, we report in vitro studies of the human flubromazolam metabolism analyzed by liquid chromatography high‐resolution mass spectrometry (LC‐HRMS). In vitro investigations were carried out in pooled human liver microsomes (pHLM) and recombinant cytochrome P450 (CYP)‐enzymes. To confirm those metabolites detected in vitro, authentic samples obtained from two forensic cases were also analyzed by LC‐HRMS. Additionally, determination of the unbound fraction of flubromazolam in pHLM and in plasma was performed by equilibrium dialysis with subsequent prediction of its hepatic clearance ( CLH ) using well‐stirred and parallel‐tube models. Additional findings obtained by routine screening methods of these forensic cases are also reported. Studies using incubations with nicotinamide adenine dinucleotide phosphate‐fortified pHLM with or without uridine 5'‐diphosphoglucuronic acid and incubations with CYP‐enzymes identified the main metabolic pathway of flubromazolam as hydroxylation on the α‐ and/or 4‐position mediated by CYP3A4 and CYP3A5, with subsequent glucuronidation of the hydroxylated metabolites as well as of the parent drug. Further, α‐hydroxy‐flubromazolam and its corresponding glucuronide were detected in vivo together with the N ‐glucuronide of flubromazolam. The predicted CL H of flubromazolam using the well‐stirred and parallel‐tube models were 0.42 and 0.43 mL/min/kg, respectively. Based on the data presented here, flubromazolam is primarily metabolized by CYP3A4/5 with a high protein‐binding and a predicted low clearance. Analysis of authentic samples suggested that analytical targets for flubromazolam should be the compound itself and α‐hydroxy‐flubromazolam. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Flubromazolam is adesigner benzodiazepine first detected as an abused drug in 2014. By using various in vitro system, we identified CYP3A4 and CYP3A5 as the main contributing CYP enzymes in mediating the (x‐hydrody‐(M1), 4‐hydrody‐(M2) and(a, 4)–dihydroxy‐flubromazolam(M3) in human liver microsomes (pHLM). Analysis of authentic samples revealed flubromazolam, M1 and the subsequently glucuronidated metabolite (M5 ), as well as the directly N‐ glucuronidated flubromazolam (M6 ) to be excreted in urine, whileM2 and the corresponded glucuronide (M4) were not detected in this specimen. Finally, further studies showed flubromazolam is a highly protein‐bound drug with a predicted low clearance.